Badania nad oryginalnością zasobów przedsiębiorstwa - Krupski, Rafał (Research over originality of supplies enterprise, 2006)
The article presents the results of research about the level of resource originality in entrepreneurs which can be the basis of strategy identification. Other results concerns the importance of different resources in occasions usage processes. The deductively constructed model of resource strategy structure is also presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 97-105